PEMANFAATAN JENIS ROTAN OLEH MASYARAKAT DUSUN MUNGGUK MERANANG KECAMATAN SUNGAI LAUR KABUPATEN KETEPANG - Sarikun, Sarikun; M, Iskandar A; Hardiansyah, Gusti (Universitas Tanjungpura, 2019)
Forest is a source of germplasm that has the potential to meet a variety of human needs such as: food, shelter, medicines and handicrafts. This species of rattan plant is one of the non woodÂ forest products utilized by the people of Mungguk Meranang village and the species of rattan that are widely used as matting, rigging, and as vegetables. The purpose of this study was to determine the type of rattan, the species of activity made from rattan and the income of the rattan craftsmen comercial in Mungguk Meranang villaget, Sungai Laur District, Ketapang Regency. The results of the study carried out there are 10 types of rattan plants that are utilized, 12 types of woven made from rattan and net income of the community of Rp. 1,322,866 / year with a maximum net income of Rp. 2,268,000 / year and minimum net income of Rp. 276,000 / year.Keywords: Korthalsia, Calamus and Daemonorops